Assessment of stromal eosinophilia in cutaneous squamous cell carcinoma - Abu deka, Farah Falah Hassan (AL-Kindy College Medical Journal, 2019)
Background: Tumor associated tissue eosinophilia (TATE) has been described in a variety of neoplasms. In regard to squamous cell carcinoma, some studies worldwide done to assess stromal eosinophilia in oral and cervical squamous cell carcinoma. The objectives of this study is to evaluate the association of stromal eosinophilic infiltration of cutaneous squamous cell carcinoma and to detect the significance of this association.Aim of the studyThe aim of our study is to establish the relationship between the degree of stromal eosinophilia and the level of invasion and the histological grade in cutaneous squamous cell carcinoma.Methods: In this retrospective study done at the histopathology department of al Wasity teaching hospital for orthopedic and plastic surgery in Baghdad, all paraffin embedded blocks for excisional biopsies diagnosed as   primary cutaneous squamous cell carcinoma from December 2015 to January 2017 were retrieved. Incisional biopsies and those with margin positive tumor cells were excluded. After a   careful evaluation  for histological grading and assessment of level of invasion  according to an established histological criteria , the assessment of tissue eosinophils was done by three pathologist through counting  eosinophils in tumor stroma in  10 high power field using  a light microscope  and categorized as none (0,),low (1-4),medium (5-19)and high (more than 20).Results : of 56 cases of primary cutaneous squamous cell carcinoma 48(85.7%) cases were conventional .The  mean age was  43.14 ± 1.76  .Regarding conventional squamous cell carcinoma ,of 48 cases 30(62.5)  were well differentiated,16(33.3%) had clarck level III,18(37.5%) had clarck level IV and 14(29.1%) had Clark level V .There is a significant statistical relationship between histological grading of tissue eosinophilia and level of invasion  with p value 0.044 and a non-significant relationship with degree of differentiation.Conclusion :The majority of cutaneous squamous cell carcinomas were conventional well differentiated   with a mean age   in the fifth decade of life ,a male predominance and  often had a degree of stromal eosinophilia that is strongly associated with the level of invasion .Thus more Intense tissue eosinophilia is correlated with a higher level of stromal  invasion. The significance of such an association should be regarded as either a potential predictive tool for stromal invasion in small incisional biopsy or as a prognostic indicator that could be included in the pathology report for conventional squamous cell carcinoma